Clinical Efficacy Observation of Acupuncture Treatment for Nonarteritic Anterior Ischemic Optic Neuropathy - Qin, Yali (Evid Based Complement Alternat Med, 2015)
Objective. To determine whether acupuncture treatment impacts the clinical efficacy of degenerative damage of the optic nerve caused by nonarteritic anterior ischemic optic neuropathy (NAION). Methods. 69 patients (93 eyes) with NAION who had been treated by acupuncture which is performed on different acupoints related to eyes by vertical insertion or Fingernail-pressure needle insertion. The best corrected visual acuity, mean defect (MD) and mean light sensitivity (MS) of the visual field, and latency and amplitude of pattern visual evoked potential (P-VEP) were compared before and after treatment. Results. After 2, 4, and 8 weeks of treatment, the total effective rates of visual acuity improvement were 74.19%, 78.89%, and 81.71%, respectively, and the decreased MD and increased MS were both statistically significant (P < 0.01). When compared with the situation before treatment, the average latency of the P(100) wave was significantly reduced (P < 0.05), and the average amplitude was improved with no statistically significant difference (P > 0.05). Conclusions. Acupuncture treatment could obviously improve the visual function of patients with NAION and be used as complementary and alternative therapy in clinic.